PENGEMBANGAN BUKU AJAR BIOLOGI BILINGUAL SMP KELAS IX SEMESTER I YANG TERINTEGRASI DENGAN KURIKULUM CAMBRIDGE - Nurul Fadhilah; Yusminah Hala; adnan adnan (UNM Journal of Biological Education, 2018)
The model of research that used in this research was Research and Development (R&D). This research aims to produce bilingual biology textbook for Junior High School grade IX semester I which integrated by Cambridge curriculum that valid. The subjects of the research are two biologists, a biology teacher, and twenty eight student’s grade IX semester I at Junior High School of 12 Makassar. This research was conducted by using modification of 4-D development model, it consist of Define, Design, and Develop. Disseminate stage did not conducted because of fund and time limit of the research. The technique of data collection in this research was the data from validation results of bilingual biology textbook that obtained from validation questionnaire which filled by validator, and small group test questionnaire which filled by students. The data collected were analyzed by using statistics descriptive analysis. Biology bilingual textbook that developed has components that are Start Lab, Mini Lab, Biology’s Job, Bio Facts, Bio Online, reading check, Bio Lab, Vocabulary, Scientist, Review, Think Critically and Assessment. The result of the research showed that the average total score of biology bilingual textbook validity categorized valid (4,4). The result of the students responses categorized into very good (71,19%), good (23,09%), quite good (5,48%), and less good (0,24%). Based on this research result, it can be concluded that the bilingual biology textbook for Junior High School grade IX semester I has had a high degree of validity.